PELATIHAN LARI AEROBIK 400 METER TIGA REPETISI DUA SET DAN DUA REPETISI TIGA SET SELAMA 6 MINGGU SAMA-SAMA MENINGKATKAN KECEPATAN JALAN CEPAT 3000 METER SISWA KELAS VII SMPN 11 DENPASAR - Dixon E.M. Taek Bete; I Ketut Tirtayasa; I Made Jawi (Sport and Fitness Journal, 2014)
Monitoring the author has been in SMP 11 Denpasar.They had never achieved maximum performance (champion) in the number of brisk walking.Because by declining student motivation, student interest because it appears more inclined to form other sports, such as volleyball ball games, soccer, futsall, table tennis or badminton or perhaps training methods that do not follow the principles of training required. The purpose of this training is to determine an increase in the speed of a brisk walk 3000 meters against both treatment groups. This study used an experimental method. Population is taken from class VII SMP Denpasar. This study used an experimental method. Population is taken from class VII SMP Denpasar. Samples are 32 people drawn randomly from the population who meet the inclusion and exclusion criteria. The number of samples divided into two groups with each group consisting of 16 people. The training is done with a frequency 4 times a week for 6 weeks. The first group was given 400-meter aerobic training run two sets of three reps and group II aerobic training 400 meter run three sets of two reps. Data in the form of brisk walking 3000 meter results taken before and after training. The data obtained were tested using SPSS computer program. The data were normally distributed and homogeneous so that further tested using paired t-test to compare mean values ??before and after training between each group, while the independent t-test to determine differences in mean values ??between the two groups. Paired t-test results of Group I and Group II were significantly increased (p <0.05). The results of independent t-test found that the two groups before the training was not significant (p> 0.05), whereas both groups after training pace brisk walking are equally increased (p> 0.05). Conclusion that aerobic training 400 meter run two sets of three reps and three sets of two reps for 6 weeks together (not significant) increase the speed of a brisk walk 3000 meters class VII SMP 11 Denpasar.